Electric Plan - Rizky, Adhinda Septhia Nur; Al Fathin, Deva Shofa; Nurapriliansyah, Helmi; S., Nadia Difa’i Mutmainah; Suwandi, Tri; Rusdiana, Dadi (Universitas Pendidikan Indonesia (UPI), 2021)
Energy consumption that still use fossil energy or non-renewable energy has a negative impact on the environment. Alternative energy innovations or renewable energy have also begun to be developed to replace fossil energy or non-renewable energy. This study aims to determine whether other types of plants that wasn’t used by Helder could also generate electricity and reduce the impact of non-renewable energy. This research was conducted by placing electrodes on the soil close to the roots of the plants. In this experiment, we used 3 types of plants that are common at home, namely Chrysanthemum, Orchid, and Red Begonia. The results show that there is indeed a very small flow of electricity, this could possibly due to various factors. If this experiment continues to develop, the possibility of green-electrical energy could be more than just a dream. Based on experiments using a prototype that we have done, the three plants have the potential to produce electric currents in the range of 0.02mA-0.65mA.